PENGARUH CAFFE ATMOSPHERE DAN EXPERIENTIAL MARKETING TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION DI CAFFE BLACKDEW PACET MOJOKERTO - Ma'arif, Syaifudin; Novie, Muhafidhah; Kamila, Edita Rachma (JURNAL LENTERA BISNIS, 2026)
The purpose of this study is to ascertain how Caffe Atmosphere and Experiential Marketing affect Customer Loyalty, with Customer Satisfaction serving as a mediator, particularly among Caffe Blackdew Pacet patrons in Mojokerto. Partial Least Squares (PLS) is a quantitative technique used in this investigation. A structured model was used to analyse the data, which were gathered via a questionnaire with a Likert scale. The findings show that customer loyalty is significantly impacted by caffeine atmosphere and experiential marketing. It was also shown that this association was mediated by customer satisfaction. These results imply that improving the ambience and experiences offered to patrons will make them happier, which may have an impact on how devoted they are to the café. This study shows that café managers can greatly benefit from creating successful marketing tactics. In order to compete more successfully with other cafés, the objective is to improve the comfortable experience and increase client satisfaction.